2001
DOI: 10.1037/0735-7044.115.1.175
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of adrenal and reproductive hormones to the opposing effects of stress on trace conditioning males versus females.

Abstract: Exposure to an acute stressful experience facilitates classical conditioning in male rats but impairs conditioning in female rats (T. J. Shors, C. Lewczyk, M. Paczynski, P. R. Mathew, & J. Pickett, 1998; G. E. Wood & T. J. Shors, 1998). The authors report that these effects extend to performance on the hippocampal-dependent task of trace conditioning. The stress-induced impairment of conditioning in females was evident immediately, 24 hr and 48 hr after stress, depending on the stage of estrus. Moreover, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
169
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 87 publications
(127 reference statements)
13
169
0
1
Order By: Relevance
“…In rats, exposure to an acute stressful event can facilitate learning in males, but impairs performance in female rats. 311,312 Furthermore, exposure to an elevated plusmaze, a rodent anxiety test, leads to decreased 5-HTergic activity in the dorsal raphe nuclei in female rats, but to decreased 5-HTergic activity in the medial raphe nuclei in males. 101 There is also data to indicate that male rats may adapt better to stress than females.…”
Section: Biopsychological Interactionsmentioning
confidence: 99%
“…In rats, exposure to an acute stressful event can facilitate learning in males, but impairs performance in female rats. 311,312 Furthermore, exposure to an elevated plusmaze, a rodent anxiety test, leads to decreased 5-HTergic activity in the dorsal raphe nuclei in female rats, but to decreased 5-HTergic activity in the medial raphe nuclei in males. 101 There is also data to indicate that male rats may adapt better to stress than females.…”
Section: Biopsychological Interactionsmentioning
confidence: 99%
“…Using this paradigm we have found that exposure to an acute stressor of inescapable tailshocks or forced swimming facilitates classical eyeblink conditioning 24 h later in male rats (Beylin & Shors, 1998;Shors, Weiss, & Thompson, 1992). In females, however, exposure to these same stressors impairs eyeblink conditioning (Shors, Lewczyk, Pacynski, Mathew, & Pickett, 1998;Wood, Beylin, & Shors, 2001;Wood & Shors, 1998). In both cases, stress is thought to modulate learning directly, but an alternative interpretation is that prior stressor exposure affects performance during eyeblink conditioning, and not learning, per se.…”
Section: Introductionmentioning
confidence: 97%
“…
AbstractExposure to an acute stressor of inescapable swimming or intermittent tailshocks impairs classical eyeblink conditioning 24 h later in female rats (Wood, Beylin, & Shors, 2001). This effect is often attributed to a deficit in "learning," but since stress has been shown to induce analgesia (Jackson, Maier, & Coon, 1979), an alternative explanation is that stressor exposure reduces conditioning by lessening the perceived intensity of the unconditioned stimulus (US).
…”
mentioning
confidence: 99%
“…Notably, E 2 increases 3α,5α-THP in the hippocampus [8,9,21], which is an important area for affective processes [17]. Further, stressful or challenging environmental experiences increase biosynthesis of E 2 and 3α,5α-THP [22][23][24][25]. As such, we were interested in the effects of E 2 and/or 3α,5α-THP on behaviors that may promote sexual interactions (exploration, anxiety, social behaviors) and whether actions of E 2 and/or 3α,5α-THP in the VTA are sufficient to modulates these behaviors.…”
Section: Introductionmentioning
confidence: 99%